Determination of Selling Prices for Small and Medium Enterprises Gendhis Apple Agroindustry in Bumiaji District, Batu City - Syafira Athaya Sitania; Suhendri, Hendrik; Sri Indah (International Journal of Management and Business, 2025)
This study aims to analyze the selling price determination strategy at the Gendhis Agroindustry Apple Small and Medium Enterprises (SMEs) located in Bumiaji District, Batu City, with a focus on the application of the Mark-Up Pricing method in calculating product selling prices. Methods: The method used in this study is a quantitative method with a markup pricing approach. Researchers collect data through interviews, observations, and documentation that includes the cost of raw materials, labor, and factory overhead involved in production. The data obtained is used to calculate the selling price of the product using the Mark-Up Pricing method. The study's results indicate that SME Gendhis Agroindustry Apple currently sets the selling price based on a rough estimate without detailed calculations. This causes a significant difference between the market price and the price calculated using the Mark-Up Pricing method. With a 40% mark-up, the selling price of apple milk pie products is IDR 3,072 per piece and apple brownie chips are IDR 4,276 per piece. Although this method is simple and effective in covering production costs and profit margins, this method does not take into account external factors such as consumer purchasing power and the level of market competition, The conclusion of this study shows that the application of the Mark-Up Pricing method is effective in covering production costs and profit margins. However, the lack of detailed calculations and external factors such as consumer purchasing power and market competition need to be considered. It is recommended that SMEs record production costs in detail and conduct market analysis to adjust selling prices to consumer purchasing power and market conditions.